????? ????? ????? ??????? ??????? ?????? ?????? ??????? 2013 ?? ??????? ???????? ???????? ???????? THE PROCESS OF ARABIC TEACHING WITH SCIENTIFIC APPROACH BY 2013 CURRICULUM IN SEVENTH CLASS MTSN BATUSANGKAR - Ahmat Nusir (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
Abstract: The purpose of this study is to describe the process of learning Arabic with a scientific approach to the 2013 curriculum at MTsN Batusangkar. The research methodology used is ethnography. The research steps are to collect data from interviews, observations, and questionnaires. The results of the study of the Arabic language learning process with a scientific approach in the 2013 curriculum in seventh grade MTsN Batusangkar, from the learning steps using a scientific approach (observing, asking questions, gathering information, associating, and communicating) showed good results. This is inseparable from the encouragement and enthusiasm of students in learning Arabic using a scientific approach. This study concludes that the scientific approach is suitable for students in learning Arabic, which is complete learning facilities and the ability of teachers to use learning media such as computers, LCDs, and so on related to learning materials.